EMPOWERMENT OF RESERVE COMPONENTS IN STATE DEFENSE EFFORTS IN THE AREA OF KODAM III/SILIWANGI TO SUPPORT THE LAND DEFENSE STRATEGY - Tjahjono Tjahjono; Kamistan Hadirin; Lukman Yudho Prakoso; Sunarko Sunarko; Mitro Prihantoro; Heri Abriyadi (Sekolah Tinggi Pariwisata Mataram, 2023)
Indonesia adheres to the Universal Defense System in dealing with military and non-military threats, which involve citizens, territories and other national resources. Article 7 paragraph 1 of Law number 3 of 2002 concerning National Defence, states that National Defense is organized by the government and is prepared early on with the national defense system. In this system, the main component is the TNI, supported by reserve components and supporting components. The National Resources prepared to strengthen the strength and capability of the main components of national defense are Reserve Components, in this case human resources. This formation is voluntary, given basic military training, determination and development of both administration and capabilities and deployment through mobilization and only based on orders from the President through the approval of the DPR. A strategy is needed so that the potential of the Reserve Component can be maximized in the effort to defend the country in the Kodam III/Siliwangi area as part of the land defense strategy. The research objective is to analyze the empowerment of Reserve Components in an effort to defend the country to support land defense strategies. This study uses a qualitative research method with a phenomenological approach. The data obtained from the informants who have been determined are then analyzed using qualitative analysis techniques. The results of the study show that the development of Reserve Components and the empowerment of Reserve Components have not been fully implemented because they are hampered by regulations in the use of Reserve Components and their budgeting. From the data above it can be concluded that Kodam III/Siliwangi carried out the formation of the Reserve Component in accordance with the applicable law, empowerment, in this case involvement in activities related to defending the country has not been carried out, but several Reserve Component personnel have been included in the training organized by Kodam III/ Siliwangi. Advice that can be given from the conclusions above is that it is necessary to revise regulations regarding the use of Reserve Components to be involved in activities related to defending the state in order to maintain the ability to defend the state.